Household Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 in the United States: Living Density, Viral Load, and Disproportionate Impact on Communities of Color. (12th August 2021) - Cerami, Carla; Popkin-Hall, Zachary R; Rapp, Tyler; Tompkins, Kathleen; Zhang, Haoming; Muller, Meredith S; Basham, Christopher; Whittelsey, Maureen; Chhetri, Srijana B; Smith, Judy; Litel, Christy; Lin, Kelly D; et al.
Abstract: Background: Households are hot spots for severe acute respiratory syndrome coronavirus 2 transmission. Methods: This prospective study enrolled 100 coronavirus disease 2019 (COVID-19) cases and 208 of their household members in North Carolina though October 2020, including 44% who identified as Hispanic or non-White. Households were enrolled a median of 6 days from symptom onset in the index case. Incident secondary cases within the household were detected using quantitative polymerase chain reaction of weekly nasal swabs (days 7, 14, 21) or by seroconversion at day 28. Results: Excluding 73 household contacts who were PCR-positive at baseline, the secondary attack rate (SAR) among household contacts was 32% (33 of 103; 95% confidence interval [CI], 22%–44%). The majority of cases occurred by day 7, with later cases confirmed as household-acquired by viral sequencing. Infected persons in the same household had similar nasopharyngeal viral loads (intraclass correlation coefficient = 0.45; 95% CI, .23–.62). Households with secondary transmission had index cases with a median viral load that was 1.4 log10 higher than those without transmission ( P = .03), as well as higher living density (more than 3 persons occupying fewer than 6 rooms; odds ratio, 3.3; 95% CI, 1.02–10.9). Minority households were more likely to experience high living density and had a higher risk of incident infection than did White households (SAR, 51% vs 19%; P = .01). Conclusions: Household crowding in the context of high-inoculum infections may amplify the spread of COVID-19, potentially contributing to disproportionate impact on communities of color. Abstract : Households are hot spots for severe acute respiratory syndrome coronavirus 2 transmission. In the United States, household crowding in the context of high-inoculum infections may amplify the spread of COVID-19, potentially contributing to disproportionate impact on communities of color.